Actividad antibacteriana in vitro de las fracciones del extracto etanólico de la corteza de Tynanthus panurensis (clavo huasca) - Romero Valles, Debhora Malu (2022)
The purpose of this work was to determine the in vitro antibacterial activity of fractions (A, B, C and D) of the ethanolic extract of the bark of Tynanthus panurensis (clavo huasca) against S. aureus and E. coli. The plant sample was collected from the Experimental Center for Medicinal Plants (Botanical Garden Arboterum) of the Faculty of Agricultural Sciences of UNAP; likewise, the bacterial strains were donated by the National Institute of Health. In vitro antibacterial activity was evaluated using the "Kirby-Bauer" disk diffusion method, where the antibiotics meropenem, ciprofloxacin, and gentamicin were used as positive controls. Results: the in vitro antibacterial activity by the disc diffusion method, at concentrations of 1300 mg/ml, of the fractions of the ethanolic extract of the bark of T. panurensis; for S. aureus, inhibition halos of 15 mm and 18 mm were observed for fractions “A and B”, respectively, fractions “C and D” did not present inhibition halos; on the other hand, for E. coli all fractions were resistant. It is concluded that S. aureus is sensitive and E. coli is resistant to fractions of the ethanolic extract of the bark of Tynanthus panurensis (clavo huasca).